A Sterically Hindered Derivative of 2, 1, 3‐Benzotelluradiazole: A Way to the First Structurally Characterised Monomeric Tellurium–Nitrogen Radical Anion. Issue 64 (8th October 2020) - Petrov, Pavel A.; Kadilenko, Evgeny M.; Sukhikh, Taisiya S.; Eltsov, Ilia V.; Gushchin, Artem L.; Nadolinny, Vladimir A.; Sokolov, Maxim N.; Gritsan, Nina P.
Abstract: Interaction of the tetradentate redox‐active 6, 6′‐[1, 2‐phenylenebis(azanediyl)]bis(2, 4‐di‐ tert ‐butylphenol) (H4 L) with TeCl4 leads to neutral diamagnetic compound TeL (1 ) in high yield. The molecule of 1 has a nearly planar TeN2 O2 fragment, which suggests the formulation of 1 as Te II L 2−, in agreement with the results of DFT calculations and QTAIM and NBO analyses. Reduction of 1 with one equivalent of [CoCp2 ] leads to quantitative formation of the paramagnetic salt [CoCp2 ] + [1 ] .−, which was characterised by single‐crystal XRD. The solution EPR spectrum of [CoCp2 ] + [1 ] .− at room temperature features a quintet due to splitting on two equivalent 14 N nuclei. Below 150 K it turns into a broad singlet line with two weak satellites due to the splitting on the 125 Te nucleus. Two‐component relativistic DFT calculations perfectly reproduce the a ( 14 N) HFI constants and A ∥ ( 125 Te) value responsible for the low‐temperature satellite splitting. Calculations predict that the additional electron in 1 .− is localised mainly on L, while the spin density is delocalised over the whole molecule with significant localisation on the Te atom (≥30 %). All these data suggest that 1 .− can be regarded as the first example of a structurally characterised monomeric tellurium–nitrogen radical anion. Abstract : Radical route : Reduction of sterically hindered 2, 1, 3‐benzotelluradiazole derivative 1 opened the way to its reduced radical anion form 1 .−, and both were isolated and characterised by XRD. The solution EPR spectrum of 1 .− was recorded in a wide temperature range (77–300 K), and the values of a ( 14 N) and A ∥ ( 125 Te) were determined. Two‐component relativistic DFT calculations perfectly reproduce these values and predict that the spin density is delocalised over the whole molecule with high spin population of Te and N atoms.